Inhibition of the p38 MAPK pathway as a strategy to overcome tumour immune suppression in CD1c+ dendritic cells - Chisanga, Chrispin (2024)
Introduction: Harnessing the potential of the immune system to destroy and eliminate cancer cells has been a long-term dream for many researchers in the field of cancer immunotherapy. The licencing of immune checkpoint inhibitors (ICI) and targeted therapies for malignancies such as malignant melanoma confirms the value of immune responses with important advances in survival being achieved despite some notable toxicity. Despite these major advances, there remains a keen interest in new treatments with improved efficacy and safety profiles and the exploration of adoptive immunotherapy with dendritic cells (DC) remains topical. Dendritic cells belong to a heterogeneous population of professional antigen presenting cells (APC) and reside in peripheral tissues and lymphoid organs. Previously, our group described loss of function of myeloid CD1c+ DC in patients with advanced melanoma and showed promising data to support the concept of restoring immune function by inhibiting mitogen activated protein kinase (MAPK) signalling pathways in these cells. Notably, inhibition of p38 MAPK (p38i) with small molecule research inhibitors was shown to increase the balance of IL-12:IL-10 secretion to favour the differentiation of Th1 responses. This thesis explored the impact of inhibiting p38 MAPK with candidate small molecules suitable for clinical use on the chemotaxis of CD1c+DC.